Incidence and Risk Factors of Venous Thromboembolism in Childhood Acute Lymphoblastic Leukaemia – a Population-Based Analysis of the Austrian Berlin-Frankfurt-Münster (BFM) Study Group. (17th February 2023) - Gidl, Anna; Füreder, Anna; Benesch, Martin; Dworzak, Michael; Engstler, Gernot; Jones, Neil; Kropshofer, Gabriele; Pötschger, Ulrike; Poyer, Fiona; Tamesberger, Melanie; Witt, Volker; Mann, Georg; et al.
Abstract: Venous thromboembolism (VTE) is a well-known complication of the treatment of pediatric acute lymphoblastic leukemia (ALL). We analyzed 1026 ALL patients 1–18-years-old, who were enrolled into the AIEOP-BFM ALL 2000 or 2009 studies in Austria, with regard to the incidence and risk factors of VTE. The 2.5-year cumulative incidence (CI) of VTE ≥ grade 2 was 4%±1% (n = 36/1026). Twenty VTE (56%) were found in the central nervous system (19 cerebral venous sinus and 1 cortical vein thrombosis), and 16 (44%) at other sites (7 deep vein thromboses (DVT) of the lower extremity, 4 DVT of the upper extremity, 4 central venous line-thromboses, 1 pulmonary embolism). Most VTE occurred during induction and early consolidation therapy (81%) and were associated with L-asparaginase within 4 and corticosteroids withing 1 week(s) preceding the event (89 and 86%, respectively). In multivariable analysis, two independent risk factors were found. Patients 10–18-years-old had an increased (hazard-ratio: 2.156, p = 0.0389), whereas treatments in trial AIEOP-BFM ALL 2009 had a lower risk for VTE (hazard-ratio: 0.349, p = 0.0270). In conclusion, the 2.5-year CI of VTE among our pediatric patient cohort was <5% and adolescent age was the main patient-related risk factor. This older age group might benefit from primary prophylactic measures.